The influence of a pre-competition training program containing plyometric exercises on the training of performance handball players - Cazan, F.; Georgescu, A.; Gidu, D. V.; Musat, G. (Journal of Physical Education and Sport, 2022)
This study shows the opportunity to use plyometric workouts in the pre-competitive period to improve jumping, for men's handball players. The main purpose of this paper is to demonstrate the usefulness of a pre-competitive PT program. We will assume that if we use an 8-week PT program, we will get effective results in jumping performance tests. There are 18 research subjects, members of Team Handball, with an average age of 22.64 (±1.28 years), stature 192.41 (±3.22 cm), body mass 94.23 (±7.61 kg). The team is playing in the National Championship, Second League. The study was conducted during the precompetitive period. The subjects were tested twice, before and after applying the work program that was conducted for 8 weeks. The subjects completed the following in this order: squat jump, counter-movement jump with arm-swing, continuous 6 jumps with straight legs without arm-swing. Within eight weeks during the two tests, the team included in the training process, the new program designed to improve the jumping performance. The program provides three workouts per week, on Monday, Wednesday and Friday, 30 min each, included in the team's training session. After 8 weeks of training, the group made significant (p=0.05) improvements in SJ (from 46.44 ± 1.54 to 50.50 ± 1.47 cm; 8.73%), CMJ (34.83 ± 1.54 to 37.44 ± 1.15 cm; 7.5%) and CJSL (from 29.78 ± 1.26 to 32.61 ± 1.33 cm; 9.51%) performance compared with the initial test. The research hypothesis was confirmed, an 8-week pre-competitive PT program with three workouts per week, can get effective results in jumping performance tests.